A Study on Impact of Performance Management System on Organization - Panda, Sitansu; Reddy, K. Jayarama (Penerbit Universiti Malaysia Pahang, 2016)
Performance Management System (PMS) is developed and implemented in organizations to achieve organizational goals effectively. PMS is vital for an organization. In this paper, the association between PMS and Organizational Effectiveness (OE) is explored. The study reveals that there is an association between PMS and OE. The finding is also in line with the previous research studies emphasizing the impact of PMS on OE. The relationship and impact of the variables are justified by the respective statistical values. It establishes the dependence of organizational outcomes on PMS.